Perceptions of vaginal microbicides as an HIV prevention method among health care providers in KwaZulu-Natal, South Africa - Mantell Joanne E; Mtimkulu James; Morar Neetha S; Ramjee Gita; Gharbaharan Varanna (AIDS Research and Therapy, 2007)
Abstract Background The promise of microbicides as an HIV prevention method will not be realized if not supported by health care providers. They are the primary source of sexual health information for potential users, in both the public and private health sectors. Therefore, the aim of this study was to determine perceptions of vaginal microbicides as a potential HIV prevention method among health care providers in Durban and Hlabisa, South Africa, using a combination of quantitative and qualitative methods. Results During 2004, semi structured interviews with 149 health care providers were conducted. Fifty seven percent of hospital managers, 40% of pharmacists and 35% of nurses possessed some basic knowledge of microbicides, such as the product being used intra-vaginally before sex to prevent HIV infection. The majority of them were positive about microbicides and were willing to counsel users regarding potential use. Providers from both public and private sectors felt that an effective microbicide should be available to all people, regardless of HIV status. Providers felt that the product should be accessed over-the-counter in pharmacies and in retail stores. They also felt a need for potential microbicides to be available free of charge, and packaged with clear instructions. The media was seen by health care providers as being an effective strategy for promoting microbicides. Conclusion Overall, health care providers were very positive about the possible introduction of an effective microbicide for HIV prevention. The findings generated by this study illustrated the need for training health care providers prior to making the product accessible, as well as the importance of addressing the potential barriers to use of the product by women. These are important concerns in the health care community, and this study also served to educate them for the day when research becomes reality.